2018
DOI: 10.3390/met8060446
|View full text |Cite
|
Sign up to set email alerts
|

Improving Elevated-Temperature Strength of an Al–Mn–Si Alloy by Strain-Induced Precipitation

Abstract: Abstract:The coupled effect of strain-induced precipitation and stabilized substructure on the elevated-temperature strength of an Al-Mn-Si alloy and its thermal stability have been investigated. Prestrain significantly promotes the nucleation of nano-sized dispersoids, and strain-induced precipitation suppresses recrystallization, stabilizing substructure at elevated temperatures. Compared with the dispersoids formed during the heat treatment of as-cast alloy, substructure does not increase the coarsening rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The largest precipitate size was 55.2 µm, which is a reasonable value compared with the experimental observations. Figure 8 shows the Mn and Fe distribution of the region where the corresponding phase is indexed as Al 6 Mn. An increase in the Fe concentration is evident moving from the bottom-left corner to top-right according to the shift of the α-Al solidification front.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest precipitate size was 55.2 µm, which is a reasonable value compared with the experimental observations. Figure 8 shows the Mn and Fe distribution of the region where the corresponding phase is indexed as Al 6 Mn. An increase in the Fe concentration is evident moving from the bottom-left corner to top-right according to the shift of the α-Al solidification front.…”
Section: Resultsmentioning
confidence: 99%
“…Small changes in the concentrations of alloying elements or heat treatment conditions can readily alter the mechanical properties and product quality by modifying the microstructure. For example, Mn is alloyed in Al to enhance strength, formability, and corrosion resistance [4][5][6]. However, undesired formation of large, faceted Mn-containing precipitates in high-Mn content alloys can diminish the desired properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hot rolling or extrusion can also eliminate casting defects such as slag inclusion and porosity to further improve material properties [22e25]. Zhang et al [26] found that prerolling at room temperature significantly promoted nucleation of nanosized dispersoids and increased the number density of dispersoids in AleMneSi alloys. However, deformation at room temperature increased the risk of cracking, which increases the difficulty of manufacturing [27].…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding comprehensive properties of aluminum alloys make it a promising material in promoting lightweighting of automobiles [1][2][3][4]. However, high-strength aluminum alloys have poor ductility at room temperature, and in the traditional cold stamping process, aluminum alloys are prone to problems such as springback, cracking, and high forming resistance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%